2021
DOI: 10.3389/fpsyg.2021.676787
|View full text |Cite
|
Sign up to set email alerts
|

Bystander Roles in Cyberbullying: A Mini-Review of Who, How Many, and Why

Abstract: Cyberbullying has progressively increased due to the massive use of the internet and social networks. Bystanders constitute the largest group, occupying a key role in the evolution of the cyberbullying situation and its consequences for the victim. Research shows different ways in which bystanders behave, suggesting different types of sub-roles associated with different study variables. The objective of this literature review is to identify and characterize the roles of bystanders in cyberbullying situations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
(138 reference statements)
0
8
0
Order By: Relevance
“…Society has progressively transformed over time, showing evidence of a significant increase in technological devices and Internet use, considering in particular the mass use of cell phones that allow people to be connected at any time and place [ 83 ]. Currently, people interact on different digital platforms, where violence, aggression, hate speech, cyberbullying, and other social phenomena that negatively affect people are observed [ 20 , 24 , 25 , 26 , 28 , 59 ], and these are important for Chilean university students since 78.3% use the social network daily [ 71 ]. MD through technologies is relevant because this construct is associated with negative Internet behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Society has progressively transformed over time, showing evidence of a significant increase in technological devices and Internet use, considering in particular the mass use of cell phones that allow people to be connected at any time and place [ 83 ]. Currently, people interact on different digital platforms, where violence, aggression, hate speech, cyberbullying, and other social phenomena that negatively affect people are observed [ 20 , 24 , 25 , 26 , 28 , 59 ], and these are important for Chilean university students since 78.3% use the social network daily [ 71 ]. MD through technologies is relevant because this construct is associated with negative Internet behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…MD is linked to different negative behaviors such as online hate speech [ 20 ], racist behavior on news websites [ 21 ], hostile emotions [ 22 ], sexist memes online [ 23 ], cyberbullying [ 24 , 25 , 26 , 27 ], and increased cyberaggression and cybervictimization [ 28 , 29 , 30 ]. In addition, it has a moderating role between social network fatigue and online trolling [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of interventions that measured differences in the prevalence of CBS, none was found to be effective. This could lead us to suggest that this outcome is due to the difficulty of producing changes in this type of behavior or in the difficulty of objectively measuring these changes ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…But teens with a higher emphasis on empathy would intervene directly in any situation, whether it was anonymous or private. Over time, the higher the frequency of bystanders' cyberbullying, the lower the empathic response [29]. Some studies have shown that teenagers on average choose to be more likely to help a friend of their sex.…”
Section: Bystanders Of Cyberbullyingmentioning
confidence: 99%